Employees' psychological empowerment and performance: how customer feedback substitutes for leadership. Issue 7 (8th October 2018) - Guerrero, Sylvie; Chênevert, Denis; Vandenberghe, Christian; Tremblay, Michel; Ben Ayed, Ahmed Khalil
Abstract : Purpose: Relying on the theories of substitutes for leadership and psychological empowerment, this study aims to explore how perceptions of customer positive feedback can substitute for managers' transformational leadership in driving frontline employees' psychological empowerment and, in turn, task performance. Design/methodology/approach: The authors tested the research hypotheses with frontline employees working in 17 equipment rental stores. Employees completed a questionnaire about customer positive feedback, transformational leadership and psychological empowerment, and supervisors completed a separate questionnaire about employees' task performance. A total of 178 employee-supervisor dyads formed the final sample of the study. Findings: The results provided support for our hypotheses. Psychological empowerment fully mediated the relationship between transformational leadership and task performance. Moreover, customer positive feedback moderated the indirect relationship between transformational leadership and task performance such that it was significant and positive only when customer feedback was low. Originality/value: This paper contributes to the service marketing literature by showing that customer positive feedback can substitute for managers' leadership in helping frontline employees feeling more in control of their work and psychologically empowered. Another useful contribution for practitioners is that customers may have a positive impact on frontline employees' motivation state, which past research has little explored.